Breast Imaging Fundamentals: An Interactive Textbook (iBook and PDF Versions) - Lara Hardesty (Association of American Medical Colleges, 2015)
Abstract Introduction Sound knowledge of breast imaging fundamentals is necessary for practice as a diagnostic radiologist. With this interactive textbook, users learns the fundamentals of breast imaging and tests this knowledge with interactive multiple-choice questions. It is not intended to be a comprehensive textbook of all aspects of breast imaging. Rather, this textbook directed at diagnostic radiology residents on their first breast imaging rotation, as well as diagnostic radiology residents, fellows, or practicing radiologists who wish to refresh their knowledge of breast imaging fundamentals before examinations. Methods The interactive textbook covers the fundamentals of screening mammography, diagnostic mammography, breast ultrasound, and breast magnetic resonance imaging (MRI). The interactive textbook is viewable either with the iBook application on an iPad/Apple computer or as an interactive PDF. Results We have not performed a specific assessment of the impact of the use of this interactive textbook on our residents' performance. Our residents liked the interactive learning format and the ease of having the iPad to study on service rather than carrying a large textbook daily. Discussion The residents at our institution expressed appreciation of the multiple-choice questions integrated throughout the interactive textbook as opportunities for them to assess their growing level of knowledge in a format similar to that seen on the new board certification examinations.